Analyzes Health Data By Applying Data Science For Students in The Undergraduate Study Program in Public Health Faculty of Health Hang Tuah University Pekanbaru - Eka Sabna; Zupri Henra Hartomi; Yayang Sahira (Medikun Publisher, 2024)
Health services are one of the rapidly growing public service sectors currently, resulting in large piles of patient medical record data. This pile of data can provide valuable knowledge if processed in the right way. Data Science is a series of processes for exploring hidden knowledge patterns in large data sets. Data Science can be applied to discover knowledge patterns from patient profiles and health history data. The knowledge gained can be used for analysis and decision making, including to predict the type of disease, determine the pattern of disease spread, and see the effectiveness of treatment. So far, students from the Hang Tuah University Pekanbaru Public Health Study Program have been carrying out the data analysis process using statistics. Community Service Activities aim to enable students to use Data Science as an alternative in analyzing health data. So students can use Data Science to help analyze health data in their research. Data Science techniques discussed include Basic Concepts and Data Science Algorithms. The output of this PkM activity is increasing partner skills, publication in mass media and scientific publications